SKIN MANIFESTATIONS IN DIABETES MELLITUS - Furqan, Saira; Kamani, Lubna; Jabbar, Abdul (Journal of Ayub Medical College Abbottabad, 2014)
Background: Diabetes mellitus affects all systems of the body. Skin is also frequently involved. The aim of the study was to assess the frequency of various skin manifestations in patients with diabetes mellitus. Methods: This descriptive study was conducted at the out-patient diabetic clinics at Aga Khan University Hospital, Karachi. One hundred consecutive patients, both male and female suffering from either type-1 or type-2 diabetes mellitus were included. Results: Out of hundred patients, skin changes were present in 84% of patients. The most frequent finding was skin infections present in 29.7% of patients and the second most common finding was diabetic dermopathy found in 28.5% of patients. Other finding were: Acanthosis Nigricans in 19%, sweating complications in 14.2%, nail involvement in 10.7%, oral involvement in 5.9%, diabetic foot in 5.9%, xanthelasma in 4.7%, yellow skin in 1.1%, generalized Pruritus in 1.1%, limited joint mobility in 1.1%. Conclusion: The cutaneous manifestations are very common in our diabetic patients (84%) and it is important that they are identified and appropriately treated in diabetes follow up clinics. Key words: Diabetes mellitus, skin manifestations, infection, dermopathy